Usability Assessment of International Office Website of Diponegoro University with Scenario-Based Usability Evaluation Method and Wammi Method - Purwaningsih, Ratna; Yenifi, Ikhsan (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Website development needs to pay attention to usability aspect which consist of four factors: efficiency, effectiveness, satisfactions and error rate. The website of International Office of Diponegoro University provides academic information for Indonesian students and foreign students. The website still has some problem, especially on searching certain information. This research aims to evaluate the design of the existing website and measures the usability. A well-designed website will help users to meet theirs needs and purposes. The methods used in this study are Scenario-Based End-User Evaluation and WAMMI (Website Analysis and Measurement Inventory). Users perform a number of task on the existing website and on the redesigned website and then provide feedback for each task they have done and fill a WAMMI questionnaire as a test of memorability. This questionnaire used to test users’ memory on access process of a page from the site. The results of the data processing of usability test show that redesigned website has better value than existing website on effectiveness, efficiency, memorability and error rate.